Sport-related national pride in East and West Germany, 1992-2008: Persistent differences or trends toward convergence? - Meier, H. E.; Mutz, M. (SAGE open, 2016)
It is commonly assumed that international sport reinforces feelings of national pride and national identity. Using large-scale survey data from Germany, covering the period between 1992 and 2008, some unresolved key questions surrounding sportive nationalism are addressed. We examine the relative importance of sport as a source of national pride, analyze the sociodemographics of sportive nationalism, and describe its long-term development in East and West Germany after reunification. Results reveal that sport is an increasingly important source of pride in Germany. Sportive nationalism is more common among younger generations, males, and individuals with lower socioeconomic status. Prevailing differences between East and West Germany document persistent socialization effects of former sport-centered identity politics. Among East Germans, sport is more important for general national pride, and sportive nationalism is much more equally distributed between various social groups (with regard to age, gender, education). From 1992 to 2008, however, a trend toward convergence between East and West Germans is also demonstrated.